Update in Respiratory Diseases - Carlos Herrera Garcia, Jose (IntechOpen, 2020)
This edited volume, "Update in Respiratory Diseases", is a collection of reviewed and relevant research chapters that offer a comprehensive overview of recent developments in the field of respiratory diseases. The book comprises single chapters authored by various researchers and edited by an expert active in the respiratory diseases field. All chapters are separate but are united under a common research topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on respiratory diseases and opening new possible research paths for further novel developments.